Social justice and financial reform in the view of Sheikh Muhammad Al-khal - Sharif, Dr. Baqi Karim (Sulaimani Journal for Humanities, 2023)
Sheikh Muhammad Al-khal as a scholar, expert in Islamic sharia, active judge and also as a leader and lover of the reform school which led by the leaders Muhammad Abdo and Sheikh Muhammad Rashid Rida in Egypt. In their book, they talked about the problems, issues and challenges that face socialites in general and Kurdish society as a part of Islamic community in particular. One of the scary and destructive problems that face humanities in the past and now is lack of social justice and existence of financial corruption which its consequences and impacts spread in the society and led to destroy the entity of society in all its aspects. Sheikh Muhammad Al-khal is one of the unique Kurdish scholars who felt the danger of corruption and social injustices therefore in his books, writings and articles and statements, he talked about the ethics, value of social justice and also mentioned the causes of financial corruption and its consequences on individual and community. He also tries to identify the ways of promoting justice. In addition to that he identified the methods of reform, controlling and opposing and fighting financial corruption. The researcher would like to shed the light on role of one of the great Kurdish scholars- Sheikh Muhammad Al-khal- in the field of social justice and fighting financial corruption as an Arabic saying says: spread like wildfi
Keywords: Sheikh Mohammed Khal; Reform; Justice; Financial Reform